2018
DOI: 10.1186/s13011-018-0156-3
|View full text |Cite
|
Sign up to set email alerts
|

Drug checking: a potential solution to the opioid overdose epidemic?

Abstract: BackgroundNorth America is experiencing an overdose epidemic driven in part by the proliferation of illicitly-manufactured fentanyl and related analogues. In response, communities are scaling up novel overdose prevention interventions. Included are drug checking technologies.Main bodyDrug checking technologies aim to identify the contents of illicit drugs. These technologies vary considerably in terms of cost, accuracy, and usability, and while efforts are now underway to implement drug checking programs for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…A 2017 evidence review of drug checking technologies and research concluded that communitywide drug checking may be instrumental as part of public health responses in British Columbia, and potentially a life-saving harm reduction service [12]. At the same time, caution is advised as "[I]mplementation in the absence of rigorous evaluation could result in the wasting of precious resources, and more importantly, more lost lives to fatal overdose" [13] (p. 2).…”
Section: Introductionmentioning
confidence: 99%
“…A 2017 evidence review of drug checking technologies and research concluded that communitywide drug checking may be instrumental as part of public health responses in British Columbia, and potentially a life-saving harm reduction service [12]. At the same time, caution is advised as "[I]mplementation in the absence of rigorous evaluation could result in the wasting of precious resources, and more importantly, more lost lives to fatal overdose" [13] (p. 2).…”
Section: Introductionmentioning
confidence: 99%
“…The public health response to the opioid overdose epidemic has been challenging, given the proliferation of illicit fentanyl and fentanyl-adulterated drugs across the continent (Ciccarone, 2017; Fairbairn, Coffin, & Walley, 2017). Given the reality of a poisoned illicit drug market, there has been a variety of public health interventions implemented in various settings to address the overdose crisis, including naloxone training and distribution (Bardwell, Fleming, Collins, Boyd, & McNeil, 2019; Sherman et al, 2009; Tobin, Clyde, Davey-Rothwell, & Latkin, 2018), drug checking programs (Bardwell & Kerr, 2018; Krieger et al, 2018; Peiper et al, 2019; Tupper, McCrae, Garber, Lysyshyn, & Wood, 2018), and supervised injection sites (Boyd et al, 2018; Kral & Davidson, 2017; Strike & Watson, 2019; Wallace, Pagan, & Pauly, 2019).…”
mentioning
confidence: 99%
“…Drug checking services, wherein individuals can determine if there are contaminants, such as fentanyl, in the drugs they are planning to consume, have been recommended as one avenue to prevent poisonings [79, 80]. Various technologies are used for drug checking, including lower-cost options (e.g., fentanyl urine test strips) and more advanced laboratory techniques (e.g., mass spectrometry) [81].…”
Section: Resultsmentioning
confidence: 99%